Regulatory Mechanisms of CHD7 and PAX4 Gene Mutations on Proliferation and Apoptosis in Chondrocytes - Xu, Feng; Li, Yiyuan; Li, Datao; Dai, Yiqing; Wang, Baohong; Zhang, Ruhong (Current Molecular Medicine, 2025)
<span class=
Keywords: cartilage damage